A novel heterozygous WFS1 variant of uncertain significance in a patient with early-onset diabetes: a case report - Kan, Wen; Wang, Yunyang; Xue, Yu; Zhang, Xiaoying; Xu, Lili (Frontiers in Endocrinology, 2026)
ObjectiveTo describe the clinical presentation of a patient with early-onset diabetes and to report a novel heterozygous WFS1 variant of uncertain significance (VUS) identified in this case. This report aims to contribute to the phenotypic and genotypic spectrum of WFS1-related disorders and to discuss the challenges of interpreting VUS in complex clinical scenarios.MethodsClinical data were collected from the proband and his family members. Whole-exome sequencing was performed on the proband. Sanger sequencing was subsequently utilized to validate the identified variant in the proband and his parents. A review of the relevant literature was also conducted.ResultsA previously unreported heterozygous missense variant in the WFS1 gene, c.1550G>C (p.Arg517Pro), was identified in the proband. Segregation analysis confirmed that this variant was inherited from his father, a non-diabetic carrier; the mother did not carry the variant. The proband’s clinical phenotype was primarily characterized by early-onset diabetes and its vascular complications. No discernible neurosensory features typical of classical Wolfram syndrome—such as optic atrophy, deafness, or diabetes insipidus—were observed. Following the American College of Medical Genetics and Genomics (ACMG) guidelines, this variant was classified as one of uncertain significance (VUS). The classification was based on the following supporting criteria: PM2_Supporting (due to its extremely low allele frequency of 0.000077 in population databases) and PP3_Moderate (based on in silico predictions from the REVEL tool, which suggested a deleterious effect).ConclusionThis case report describes a novel WFS1 missense variant of uncertain significance (p.Arg517Pro) identified in a patient with early-onset diabetes. This finding contributes to the growing catalog of rare WFS1 variants and highlights the interpretive challenges they pose. It suggests that WFS1 could be considered in the genetic evaluation of selected cases of early-onset diabetes, even in the absence of full syndromic features. Prospective monitoring of asymptomatic carriers of similar variants may be warranted, pending further evidence to clarify their clinical significance.